Epidemiological profile among residents of the Sapê do Norte Quilombola Community, Espirito Santo, Brazil - Dias de Castro Luz, Ana Alice; Bubach, Susana; Silva Saccone, Laís; Santana Franco, Maila (Guará Journal, 2024)
Quilombola communities are marked by social inequalities and difficulties  in  accessing  health  services,  which  directly  impact  the health-disease process. Thus, the objective was to describe the  epidemiological  characteristics  related  to  sociodemographic  aspects,  illness,  lifestyle,  anthropometric  measurements,  and blood pressure among residents of Quilombola communi-ties  in  Sapê  do  Norte,  Espírito  Santo.  Data  collection  was  car-ried  out  by  socioeconomic  and  health  situation  information,  physical  assessment  of  blood  pressure,  waist  circumference,  weight  and  height.  Ninety  residents  of  Quilombola  communities  were  interviewed,  most  of  whom  were  women,  self-declared  black,  aged  over  fift  y  and  with  low  education.  The  results  related  to  anthropometric  measurements  revealed  that  most  of the Quilombolas evaluated were overweight or obese, increased waist circumference, high prevalence of alcoholism. More than  half  claimed  to  be  hypertensive  and  70%  of  participants  had  altered  blood  pressure  levels  (≥130/≥81  mmHg).  These  data demonstrate the vulnerability and need for intervention in these communities to prevent health problems.
Keywords: Quilombolas communities; Social vulnerability; Risk factors; Noncommunicable diseases; Social determinants of health